Information security management handbook - Tipton, Harold F.; Nozaki, Micki Krause (Boca Raton : Auerbach Publications, 2007)
A compilation of the fundamental knowledge, skills, techniques, and tools require by all security professionals, Information Security Handbook, Sixth Edition sets the standard on which all IT security programs and certifications are based. Considered the gold-standard reference of Information Security, Volume 2 includes coverage of each domain of the Common Body of Knowledge, the standard of knowledge required by IT security professionals worldwide. In step with the lightening-quick, increasingly fast pace of change in the technology field, this book is updated annually, keeping IT professionals updated and current in their field and on the job.
Access Control Systems and Methodology -- Telecommunications and Network Security -- Security Management Practices -- Applications and Systems Development Security -- Cryptography -- Security Architecture and Models -- Operations Security -- Business Continuity Planning and Disaster Recovery Planning -- Law, Investigations, and Ethics.
Includes bibliographical references and index.
1
Keywords: Computer security -- Management -- Handbooks, manuals, etc; Data protection -- Handbooks, manuals, etc